The Effect of Engine Noise on the Comfort of WA-360 Loader Heavy Equipment Operators Based on Capacity and Distance of 100, 150 and 200 cm - Sihombing, Suriady; Nababan, Wilson Sabastian; Tampubolon, Miduk; Sihombing, Hendrik (Talenta Publisher, 2024)
The existence of a limited volume of machine room and coupled with the existence of various kinds of machinery in it, both main drive machinery such as the main motor and other supporting machinery such as electric motors, compressors, pumps and so on, all of which are sources of noise, will cause high noise noise. Where heavy equipment is a tool used to simplify the work process so that it becomes faster, easier and the results are in accordance with expectations and one example is the Whell Loader WA-360 heavy machine. Therefore, research is needed to measure the level of noise produced by the Whell Loader WA-360 heavy equipment engine to operator comfort. According to NAB According to Kepmenaker No. per-51/MEN/1999,2008 and SNI 16-7063-2004, the noise level that results in hearing damage of 90 dB for workers who are working for 8 hours per day. That the threshold value for the noise of the combustion chamber of the Wheel Loader WA-360 heavy equipment engine with a bucket capacity of 3.4 and 5 tons produces a noise level of 106.5 dB with a hearing scale and it is recommended that the operator of the Whell Loader heavy equipment use Earphones while doing work.